Developmental associations with muscle morphology, physical performance, and asymmetry in youth judo athletes - Fukuda, D. H.; Beyer, K. S.; Boone, C. H.; Wang, R.; La Monica, M. B.; Wells, A. J.; Hoffman, J. R.; Stout, J. R. (Sport Sciences for Health, 2018)
Purpose: This study evaluated the contributions of somatic maturity (years from estimated peak height velocity) and training experience as developmental indicators of muscle morphology, biomechanical parameters, and bilateral asymmetries in youth judo athletes. Methods: Twenty-six judo athletes aged 8-18 years (mean±SD; age=12.9±2.6 years, maturity offset = - 0.6±2.2 years, training experience=6.1±2.9 years) completed anthropometric measurements, performance testing, and ultrasound evaluation of the vastus lateralis. Results: Somatic maturity had the greatest relationship with handgrip performance (r2=0.76-0.80; p<0.01) and lower-body plyometric ability (r2=0.23-0.72; p<0.05). Somatic maturity and training experience accounted for 72% of the variance in hopping power. Bilateral asymmetries in average/peak force and 1-/2-s force-time integration during isometric handgrip increased with training experience (r2=0.17-0.46 p<0.05). Muscle morphology (r2=0.29-0.75; p<0.01) was best related to somatic maturity. Significant differences were found between child and adolescent judo athletes in force-time curve parameters, muscle morphology, and plyometric ability. Conclusions: These results indicate that somatic maturity and training experience exert unique influences on muscle morphology, biomechanical parameters, and bilateral asymmetries in youth judo athletes.